Cytosolic domain of SIDT2 carries an arginine-rich motif that binds to RNA/DNA and is important for the direct transport of nucleic acids into lysosomes. Issue 11 (1st November 2020) - Hase, Katsunori; Contu, Viorica Raluca; Kabuta, Chihana; Sakai, Ryohei; Takahashi, Masayuki; Kataoka, Naoyuki; Hakuno, Fumihiko; Takahashi, Shin-Ichiro; Fujiwara, Yuuki; Wada, Keiji; Kabuta, Tomohiro
ABSTRACT: RNautophagy and DNautophagy (RDA) are unconventional autophagic pathways where nucleic acids are directly transported through the lysosomal membrane, then degraded inside lysosomes. We have previously shown that bitopic protein LAMP2C and putative RNA transporter SIDT2, both lysosomal membrane proteins, mediate the direct transport of nucleic acids into lysosomes and that LAMP2C interacts with the nucleic acids and functions as a receptor during RDA. Because SIDT2-mediated RDA occurs in isolated lysosomes that lack LAMP2C, in this study, we tested the hypothesis that SIDT2 itself could also interact with the nucleic acids. Our results show that SIDT2 directly binds RNA and DNA through an arginine-rich motif (ARM) located within its main cytosolic domain, and disruption of this motif dramatically impairs SIDT2-mediated RNautophagic activity. We also found that SIDT2 interacts with exon 1 of HTT (huntingtin) transcript through the ARM in a CAG-dependent manner. Moreover, overexpression of SIDT2 promoted degradation of HTT mRNA and reduced the levels of polyglutamine-expanded HTT aggregates, hallmarks of Huntington disease. In addition, a comparative analysis of LAMP2C and SIDT2 functions at the cellular level revealed that the two proteins exert a synergistic effect on RNautophagic activity and that the ARMs which mediate the interactions of SIDT2 and LAMP2C with RNA are essential for the synergy. Together, our results point out the importance of nucleic acid-binding capacity of SIDT2 for its function in translocating nucleic acids through the lipid bilayer and suggests a potential application of RNautophagy activation to reduce the expression levels of disease-causing toxic proteins. Abbreviations: ACTB/β-actin: actin beta; ARM: arginine-rich motif; CBB: Coomassie Brilliant Blue; CD: cytosolic domain; COX4I1/COX4: cytochrome c oxidase subunit 4I1; E. coli: Escherichia coli ; EGFP: enhanced green fluorescent protein; EtBr: ethidium bromide; FITC: fluorescein isothiocyanate; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GOLGA2/GM130: golgin A2; GST: glutathione S-transferase; HRP: horseradish peroxidase; HSPA5/GRP78: heat shock protein family A (Hsp70) member 5; HTT: huntingtin; HTTex1 : exon 1 of the HTT gene; LAMP2: lysosomal associated membrane protein 2; LMNA: lamin A/C; PAGE: polyacrylamide gel electrophoresis; PBS: phosphate-buffered saline; PEI: polyethyleneimine; polyQ: polyglutamine; qPCR: quantitative PCR; RAB5A: RAB5A, member RAS oncogene family; RDA: RNautophagy and DNautophagy; SCARB2/LIMP2: scavenger receptor class B member 2; SDS: sodium dodecyl sulfate; SID-1: systemic RNA interference deficient-1; SIDT2: SID1 transmembrane family member 2; WT: wild type.